Benefits of Joint Land Titling in Vietnam - Buchhave, Helle; Nguyen, Viet Cuong; Nguyen, Tam Giang; Pham, Thi Mong Hoa (World Bank, Hanoi, 2020)
The study assesses the impact of different types of land use rights certificates (LURC) on individual and household welfare, expanding on the previous research of Menon, Rodgers, and Kennedy (2016), which assessed the effects of LURCs on agricultural land on household welfare. This study considers more recent data from the Vietnam Household Living Standards Survey (VHLSS) of 2014 in addition to VHLSS data from 2002–08 and includes an analysis of LURCs for agricultural as well as residential land. The study findings are presented below in three sections. The first is an analysis of land use and LURC distribution trends based on the VHLSS data. The second draws on a group of impact evaluations that compares the effects of having different types of LURCs. We regress individuals' employment and health care outcomes on whether their name was included on a LURC. The treatment variables are whether one has been issued an agricultural or residential LURC, with controls for age, education, ethnicity, urban residence, household consumption, land area, and district. We also regress household-level outcomes—expenditures, credit levels, and incomes—on whether the household's LURC is singly or jointly titled. Notably, the distribution of LURCs is not randomized, making it difficult to estimate the causal effects of LURC status and thereby limiting the conclusions that can be drawn. The third section, using 2014 demographic data and LURC distributions, offers a cost-benefit analysis of efforts to convert and reissue all remaining singly titled LURCs to jointly titled ones. We estimate the benefit as the impact difference between single- and jointly titled LURCs as calculated in the impact evaluation section and estimate costs as those of reissuing a LURC.